Pengembangan Animasi Pembelajaran Berbasis Kinemaster untuk Meningkatkan Minat Belajar Siswa pada Materi IPA - Cahyanti, Tri Septi Agita; Utaminingsih, Retno; Rahayu, Ayu (Indonesian Journal of Learning and Educational Studies, 2023)
This study aims to; (1) describe the characteristics of learning animation video media in science learning on the material properties of objects and changes in the shape of objects in class V (2) determine the feasibility of animated video media for learning animation on material properties of objects and changes in the shape of objects in class V students (3 ) Knowing student responses to learning animation video media in science learning material properties of objects and changes in the shape of the object to increase student interest in learning in class V SDN Banteran 1. This type of research is development (Research and Development), there are 6 steps, namely potential problems, data collection, product design, design validation, design revision, and product testing. Data collection techniques were carried out by means of interviews and questionnaires. The data analysis technique in this research is using quantitative descriptive analysis. The results of this development research show the following results, (1) the characteristics of the learning video are made using the kinemaster application by taking class V material, namely the properties of objects and changes in the shape of objects which are then animated and put together to produce a kinemaster-based learning video. (2) the feasibility of the learning video media developed based on the results of the assessment, material experts obtained an average of 95.3 and obtained very good assessment criteria. The assessment from media experts obtained an average of 96 and obtained very good assessment criteria. The teacher's assessment was included in the "very good" category with a score of 94. (3) the response of the fifth grade students' interest in learning at SDN Banteran 1 was included in the "very good" category with a score of 85.2%.